Assembly and integration of conductive polypyrrole 2D nanofilm on protein nanolayer and the multiple potential applications. (16th June 2021) - Zhou, Xing; Song, Renfang; Wang, Dong; Fang, Changqing; Wang, Qiang; Deng, Jingrui
Abstract: Integrating polymer with biological matters to form hybrids or conjugates is innovative in organic/organic system with significantly promise for sensor, medical, and materials science. In this work, a uniform 2D nanofilm with the hybridization of lysozyme and polypyrrole was prepared at the air/water interface. Lysozyme was employed as the biological adhesion template, and the polypyrrole conductive layer assembled onto lysozyme film, forming a hybrid and functional film with both conductivity and bio-adhesion. The functionality and potential applications of the hybrid film were investigated by detecting the conductivity, patterning and antibacterial property. The hybrid film presents refined patterning through UV lithography, and significant antibacterial property by dissolving the outer wall of bacteria. Owing to the significant conductivity, the mechanical sensor can detect the tiny airflow changes effectively, such as tiny vibrations from human throat and basic locomotion. It supplies a path to prepare functionally flexible nanofilm in organic/organic system. Graphical abstract: Image 1 Highlights: Lysozyme supported polypyrrole hybrid film present multifunctional applications. The light transmittance can be improved for ca. 33% for the hybrid. Lysozyme significantly contributes to the patterning of the film.